Regional Features of the Pskov Folk Tales - Bolshakova, Natalia (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2014)
The paper identified and systematized ethno-linguistic, communicative and pragmatic features linguageographical Pskov tales. Study was carried out on the material of the manuscript prepared for publication of a collection of rough folk tales which have been written down in Pskovshchina during the period since the 70th of the XX century. We used the traditional system – structural methods, and methods of communicative dialects. Performed work showed that untreated tale, especially sounding, has all the features of dialect discourse, such as: pronounced intention of the speaker, dialogic speech. Content analysis allowed to reveal the historical and cultural significance of a corpus of fairy tales, which can serve as a source of information about the archaic features of traditional peasant life of the local toponymy. Language of tales reflects characteristics of the Pskov national dialects in phonetic, lexico-semantic, grammatical levels, keeping signs of boundary language space.